2021
DOI: 10.1108/ecam-03-2021-0192
|View full text |Cite
|
Sign up to set email alerts
|

Critical considerations on tower crane layout planning for high-rise modular integrated construction

Abstract: PurposeModular integrated construction (MiC) is the most advanced off-site construction technology. However, the application of MiC for high-rise buildings is still limited and challenging. One critical issue is tower crane layout planning (TCLP) to guarantee safe and efficient multiple crane-lifts for module installation, which, however, has been insufficiently explored. For filling this knowledge gap, this paper aims to systematically explore the critical considerations on TCLP for high-rise MiC to support c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…After classifying the structural types of different buildings, Wang PP [ 68 ] found that the project duration was more significantly affected by different structural types, and Hu Wenfa [ 40 ] also considered the influence of structural types in the duration prediction model. The total number of stories as a commonly used parameter in duration prediction models [ 40 ] reflects the fact that the number of building stories is a critical aspect in determining duration, and there are many studies [ 69 71 ] related to high-rise construction.…”
Section: Discussionmentioning
confidence: 99%
“…After classifying the structural types of different buildings, Wang PP [ 68 ] found that the project duration was more significantly affected by different structural types, and Hu Wenfa [ 40 ] also considered the influence of structural types in the duration prediction model. The total number of stories as a commonly used parameter in duration prediction models [ 40 ] reflects the fact that the number of building stories is a critical aspect in determining duration, and there are many studies [ 69 71 ] related to high-rise construction.…”
Section: Discussionmentioning
confidence: 99%
“…The crane selection and operation are essential tasks to manage optimization processes, analysis of the lifting cycle and probable collision; thus, lift planning, predominantly an iterative trial and error mechanism, becomes crucial for assembling modules. Improper lift planning of the cranes can result in poor stability, blind lifting, and the breakdown of cranes (OA-2) [92]. Figure 9 shows the PARETO chart for onsite assembly risks.…”
Section: Onsite Assemblymentioning
confidence: 99%
“…During the OA stage, digital technologies such as virtual and augmented reality can be used for the pre-optimization of site layout planning in high-rise VMC projects in dense urban environments, to reduce the wastage of space [92,99]. Moreover, the amalgamation of lean construction and virtual design and construction (VDC) techniques effectively reduces construction wastage at the site [48].…”
Section: Mitigation Framework For Using Digital-technology-based Circ...mentioning
confidence: 99%
“…Generally speaking, there are three main aspects that significantly affect the operational efficiency and safety of multiple tower cranes: (i) the selection and layout of multiple tower cranes on construction sites [6][7][8][9][10][11][12][13][14][15]; (ii) the improvement of path and motion scheduling [4,[16][17][18][19][20]; and (iii) the lifting schedule for each tower crane [5]. In the early stage of construction, it is necessary to choose a reasonable type of tower crane and carry out a reasonable layout of multiple tower cranes.…”
Section: Introductionmentioning
confidence: 99%